PENGARUH KEMAMPUAN KERJA,DISIPLIN KERJA, MOTIVASI KERJA TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN ADMINISTRASI UNIVERSITAS WARMADEWA - Ni Luh Sekartini (Magister Manajemen, Program Pascasarjana, Universitas Warmadewa, 2016)
Human resource is the executor of the various activities in an organization and have a very large role for the development of the organization. Employees of the University Warmadewa Denpasar guided to always be able to improve the performance, purpose of this study was to determine the significant influence of the ability to work on employee job satisfaction at the University Warmadewa, to determine the effect of work ability on the performance of employees at the University Warmadewa, to determine the effect of labor discipline on job satisfaction employees at the University Warmadewa, to determine the effect of labor discipline on the performance of employees at the University Warmadewa, to determine the effect of work motivation on employee job satisfaction at the University Warmadewa, to determine the effect of work motivation on employee performance at the University Warmadewa, and to determine the effect of job satisfaction on performance employees at the University Warmadewa. The research method is quantitative with a sample size of 62 people who are determined by the method of census data digunakanadalah primary data and secondary data both qualitative and quantitative. With SEM analysis, PLS-based research results are 1). The ability to work and no significant negative effect on job satisfaction; 2). The ability to work a significant negative effect on employee performance; 3). Labor discipline and no significant positive effect on job satisfaction; 4) Discipline of work and significant positive effect on employee performance; 5: Motivation of positive and significant effect on employee job satisfaction; 6) Work motivation positive and significant effect on employee performance; 7) Job satisfaction and no significant positive effect on employee performance.